2007
DOI: 10.1021/cb7000582
|View full text |Cite
|
Sign up to set email alerts
|

Design and Creation of New Nanomaterials for Therapeutic RNAi

Abstract: RNA interference is an evolutionarily conserved gene-silencing phenomenon that shows great promise for developing new therapies. However, the development of small interfering RNA (siRNA)-based therapies needs to overcome two barriers and be able to (i) identify chemically stable and effective siRNA sequences and (ii) efficiently silence target genes with siRNA doses that will be clinically feasible in humans. Here, we report the design and creation of interfering nanoparticles (iNOPs) as new systemic gene-sile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 26 publications
4
71
0
Order By: Relevance
“…An interesting nanoparticle delivery system has been reported that can mask the immunostimulatory effects of siRNAs, even those containing known immunostimulatory sequences 97 100 reported the use of nanoparticles composed of a lysine-based amino acid backbone with lipid functional groups (iNOPs) to deliver APOBtargeting siRNAs in vitro and in vivo. The same system was later adapted to deliver anti-miRs, which significantly decreased miR-122 expression in the liver of mice 101 .…”
Section: In Vivo Delivery Strategiesmentioning
confidence: 99%
“…An interesting nanoparticle delivery system has been reported that can mask the immunostimulatory effects of siRNAs, even those containing known immunostimulatory sequences 97 100 reported the use of nanoparticles composed of a lysine-based amino acid backbone with lipid functional groups (iNOPs) to deliver APOBtargeting siRNAs in vitro and in vivo. The same system was later adapted to deliver anti-miRs, which significantly decreased miR-122 expression in the liver of mice 101 .…”
Section: In Vivo Delivery Strategiesmentioning
confidence: 99%
“…7 Among these approaches, the most efficient systemic administration was achieved using stable nucleic acid lipid particles. 4 However, a therapeutic dose (2.5 mg/kg) of these particles, when administered in cynomolgus monkeys, caused marked liver damage.…”
Section: Introductionmentioning
confidence: 99%
“…injection of clinically relevant doses of siRNA (21). More recently, another lipid-based system termed interfering nanoparticles (iNOPs) has also demonstrated the ability to deliver siRNA in vivo (23). A key drawback of the SNALP and iNOP systems, however, is that the siRNA complexes are only passively targeted to liver.…”
mentioning
confidence: 99%